PERBANDINGAN NILAI INDEKS PRODUKTIVITAS INDUK SAPI PERANAKAN ONGOLE DI DESA WAWASAN DAN DESA PURWODADI DALAM KECAMATAN TANJUNGSARI - Andini Fradina Saly; Sulastri Sulastri; Muhammad Dima Iqbal Hamdani; Akhmad Dakhlan (Department of Animal Husbandry, Faculty of Agriculture, University of Lampung, 2020)
This study was conducted with the aim of comparing the value of the Dams Productivity Index (DPI) for weaning weight in Peranakan Ongole (PO) Cows in Wawasan and Purwodadi Dalam Villages, Tanjungsari District, South Lampung Regency. The study was conducted in November 2019 - January 2020 in Wawasan Village and Purwodadi Dalam Village, Tanjungsari District, South Lampung Regency, Lampung Province. The data used were secondary data taken from the recordings of 50 breeding cows from each village that have given birth twice. Survey method was used in this research with data sampling was done by using purposive sampling. Variables observed was date of birth, calf birth weight, calf weaning weight, weaning age, date of birth made at first parity and second parity. Result of this research showed that the Corrected Weaning Weights (CWW) in Wawasan Village (114.03 ± 10.87 kg) was higher (P <0.01) than those in Purwodadi Dalam Village (110.72 ± 10.55 kg). The average of DPI of PO cows in Wawasan Village (62.18 ± 15.57) was higher (P <0.01) than those in Purwodadi Dalam Village (51.25 ± 16.62). The top nine DPI of PO cows in Wawasan Village were B.004, C.012, B.031, C.002, C.007 and in Purwodadi Dalam Village were B.009, B.005, B.004, B.002, and B.001. Key word : Calving interval, Dams Productivity Index, Peranakan Ongole Cow, Weaning age, Weaning weight